FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG FILARIASIS DI PUSKESMAS BAGAN ASAHAN SUMATERA UTARA - ZIMLY KHATIF VALDIVIA RITONGA; NURFADLY . (JURNAL ILMIAH SIMANTEK, 2021)
Filariasis is a chronic systemic disease caused by filarial worms that are transmitted from various types of mosquitoesbiologically. Ministry of Health (2019) stated that the incidence of filariasis in Indonesia reached 10,681 cases over 34provinces in 2018. Objective: The purpose of this study was to determine the factors related to the level of public knowledgeabout filariasis based on age, gender, occupation, education level, and socio-economic. Methods: This type of research isdescriptive analytic using a cross-sectional design. The population in this study were patients who came and made visits atthe Bagan Asahan Health Center. The data collection technique was done by giving the number of written questions to therespondents. Results: The chi square test data showed that the significance level of respondents' knowledge was 0.025 byage; 0.931 by gender; 0.003 by education level; 0.003 by occupation; and 0.000 by socio-economic. Conclusion: There is arelationship between the level of knowledge with age, education, occupation, and socioeconomic.